Ethnic Favoritism: An Axiom of Politics? - Giacomo De Luca; Roland Hodler; Paul A. Raschky; Michele Valsecchi (Center for Economic Studies and ifo Institute (CESifo), 2015)
We investigate the prevalence and determinants of ethnic favoritism, i.e., preferential public policies targeted at the political leader's ethnic group. We construct a panel dataset of 2,022 ethnographic regions from 139 countries with annual observations from 1992 to 2012, and use nighttime light intensity as output measure to capture the distributive effects of a wide range of policies. We find robust evidence for ethnic favoritism: the political leaders' ethnographic regions enjoy 10% higher nighttime light intensity. We further find that ethnic favoritism is a global rather than Sub-Saharan African phenomenon, which is present in poor as well as rich countries; that political institutions have a weak effect on ethnic favoritism; that ethnic favoritism is most prevalent in ethnically fractionalized and segregated countries with long established polities; and that ethnic favoritism does not contribute to sustainable development.
Keywords: D72; R11; J15; O43; 330; ethnic favoritism; political leaders; institutions